Implementation of Diversion on Examining the Process of Children in Conflict with the Law - Zubaedah, Siti; Tira, Andi; Almusawir, Almusawir (SCAD Independent, 2023)
This research aimed to analyze the implementation of diversion in the investigation process, prosecution, and court examination of children in conflict with the law. Four police sectors (Biringkanaya police sector, Tamalanrea police sector, Tallo police sector, and Mariso police sector) have been chosen, including the state prosecutor’s office and district court of Makassar cases in 2015. This research was carried out through document searches and interviews with investigators, public prosecutors, and judges. The result showed that the diversion had been applied to every step of the investigation, prosecution, and court examination, but the achievement and implementation could have been more optimal. Overall data from the four police sectors showed that during 2015 there were 74 (seventy-four) cases of children conflicting with the law, and 7 (seven) cases had succeeded in reaching a diversion agreement (9.46%). Public prosecutors had sought diversion at the level of examination at the prosecutor’s office, but no agreement was reached. In the Makassar District Court in 2015, 223 (two hundred twenty-three) cases and 24 (twenty-four) went through the diversion agreement.